ANALISIS PENERAPAN KEBIJAKAN FAKTUR PAJAK TERBARU - Putri, Firninda Yosi Anggraini (Jurnal Akuntansi AKUNESA, 2013)
New policy changes is aimed to improve the administration system of tax invoices. A fundamental change in the numbering of series on tax invoice. In this new policy The Directorate General of Taxes will give serial number on the tax invoice, but before taxable entrepreneurs must apply for the activation code and password. This study is aimed to analyze readiness Taxable Entrepreneurs and The Directorate General of Taxes to implemention the new policy of tax invoices. Advantages of the application of this new policy is to minimize the fictitious tax invoices and disadvantages of this new policy is not effectively time needed. This new policy not only add new jobs for taxable entrepreneurs but also for tax officials to provide services Keywords: Tax invoice, The Directorate General of Taxes, taxable entrepreneurs, value added tax